Is psoas muscle area as determined by cross-sectional measurement an accurate predictor of peri-operative outcomes in adenocarcinoma of the upper gastrointestinal tract? - Divey, Mark (Division of General Surgery, 2022)
Background Radiologically measured psoas muscle area has been associated with poorer surgical outcomes. Our hypothesis is that patients with gastric cancer and lower psoas muscle area have poorer short-term surgical outcomes. Methods Individuals with gastric cancer were assessed and total psoas muscle area (TPA) in mm2 was measured at the level of the third lumbar vertebra on staging CT, using Phillips IntelloSpace PACS Enterprise version 4.4.553.50. The psoas muscle area was normalised for height (TPA mm2 /m2 ), creating the psoas muscle index (PMI). All individuals proceeding to surgery were compared in terms of PMI with correlation to short-term complications (Accordion), length of stay and mortality. In addition, PMI and tumour staging was evaluated. Results One hundred and seventy-seven individuals (115 males, 62 females, mean age of 60.8 ± 0.9) were evaluated of which sixty-eight underwent surgery (56 resections, 12 palliative bypasses). The surgical complication rate was 40% (27/68), major complications being Accordion 3 or higher at a rate of 16% (11/68) and mortality rate of 10% (7/68). The average length of stay was 10 ± 0.7 days. There was no statistically significant difference in PMI for males or females in respect to all complications, major complications, length of stay or mortality. PMI and tumour staging did not correlate. Males with gastric outlet obstruction had a statistically significant lower PMI (p <0.03) Conclusions Although low psoas muscle area has been shown to correlate with poorer surgical outcomes, we did not show this is our population undergoing surgery for gastric cancer.